Staphylococcus aureus Isolated From Retail Meat and Meat Products in China: Incidence, Antibiotic Resistance and Genetic Diversity - Wu, Shi; Huang, Jiahui; Wu, Qingping; Zhang, Jumei; Zhang, Feng; Yang, Xiaojuan; Wu, Haoming; Zeng, Haiyan; Chen, Moutong; Ding, Yu; Wang, Juan; Lei, Tao; et al. (Frontiers in Microbiology, 2018)
This study was to estimate the prevalence and characteristics of Staphylococcus aureus from 1850 retail meat and meat products in China during July 2011 to June 2016. The samples were collected covering most provincial capitals in China, including 604 raw meat, 601 quick-frozen meat and 645 ready-to-eat meat. Using the qualitative and quantitative methods, all 39 cities had S. aureus-positive samples, and S. aureus was detected in 35.0% (647/1850) of the samples. The levels of S. aureus in retail meat showed that the MPN value of the majority of the positive samples ranged from 0.3 MPN/g to 100 MPN/g. Twenty-four antibiotics were used to test all 868 S. aureus isolates for antibiotic susceptibility. Only 11 isolates (1.26%) were susceptible to all antibiotics, whereas most isolates (821/868, 94.6%) showed resistance or intermediary resistance to more than three or more antibiotics. Of these strains, 104 (12.0%) were resistant to more than 10 antibiotics. However, the most frequent resistance was observed to ampicillin (85.4%), followed by penicillin (84.6%), erythromycin (52.7%), tetracycline (49.3%), kanamycin (45.3%), telithromycin (30.1%), clindamycin (29.6%), streptomycin (21.1%), norfloxacin (20.4%), gentamicin (19.4%), fusidic acid (18.4%), ciprofloxacin (16.9%), chloramphenicol (13.1%), amoxycillin/clavulanic acid (11.0%) and others (< 10%). 7.4% of isolates (62/868) were confirmed as MRSA. By molecular typing analysis, there were 164 spa types and 111 STs were identified, including 15 novel spa types and 65 newly STs by MLST and spa typing. Despite the wide genetic diversity observed among the 868 isolates, a great proportion of the population belonged to finite number of major clones: ST1-t127 (93/868, 10.7%) and ST7-t091 (92/868, 10.6%), ST5-t002 (42/868, 4.8%), ST398-t034 (40/868, 4.6%), ST188-t034 (38/868, 4.4%), ST59-t437 (30/868, 3.5%), ST6-t701 (29/868, 3.3%) and ST9-t899 (27/868, 3.1%) in China. This study reflects S. aureus was readily detected in Chinese retail meat and meat products but the level were not very excessive. In this study, the high antibiotic resistance is alarming and raising public health concern. In additions, most of molecular types of isolates have been linked to human infections around the world, indicating that these types of S. aureus in China have a theoretical pathogenic potential.